The Role and Management of Ma’had Al-Jami’ah in Constructing Religious Character Values in PTKIN - Muhamad Yusuf; Widiya Yul; Agam Muhammad Rizki; Syafnan Syafnan; Nur Balqis (Ta'dib, 2024)
This research is motivated by the movement to spread extreme ideology increasingly facilitated by the existence of new media as a tool to inform, propagandize, and spread radical ideas. To overcome this, efforts to voice a moderate way of religion (religious character) are needed. The implementation of a system to fortify students from extremist Islamic groups is done through the implementation of ma’had. This study aims to determine, analyze the characteristics, and construct the formation of religious character in students at PTKIN throughout Indonesia. Applying qualitative research method, the data were collected .from the field based on observations and interviews and library data deriving from books, scientific articles (journals), research reports, etc. Data analysis techniques include data condensation, data presentation, and conclusion drawing. The findings of this study indicate that the characteristics of religious character in Ma’had Al-Jami’ah PTKIN throughout Indonesia can be identified by looking at intact faith, diligently performing worship, and having noble character. The role of Ma’had Al-Jami’ah in constructing religious character values in students at PTKIN throughout Indonesia is very strategic. This research contributes to PTKIN in Indonesia in accepting and graduating a very large number of students. The process of forming religious characters in students at PTKIN throughout Indonesia can be said to run simultaneously, namely through ta’lim activities, moderate insights, habituation of ubudiyah, and enactment of rules because ma’had has designed various religious activities in it in an integrated and continuous manner, aka becoming a daily routine.